Analisis Hasil Pengawasan Iklan/Promosi Suplemen Kesehatan Sebelum dan Selama Masa Pandemi COVID-19 - Angelia Puspita Nugraheni; Sarmauli Purba; Devi Riani; Wahyuri; Nurizati (Badan Pengawas Obat dan Makanan, 2021)
For entrepreneurs, advertising/promotion is a means to introduce a product. For the public, it is a means to get information about a product, so that people become very dependent on advertising/promotion. Data from BPS shows a sharp spike in online sales during the Corona Virus Disease-19 (COVID-19) pandemic, which was influenced, among other things, by government policies to limit activities outside the home. As a result, the need for health supplements has increased during the COVID-19 pandemic; several times, there have been stock shortages due to panic buying. Business actors can use this momentum for advertising/promote products that do not comply with the provisions to increase product sales, thus possibly resulting in a significantly different level of advertising/promotional violations from before the COVID-19 pandemic. This study aims to analyze the results of supervision of health supplement promotion/advertising before the COVID-19 pandemic (2018-2019) and during the COVID-19 pandemic (2020-July 2021) to determine the significance level of differences in advertising/promotional violations before and during the pandemic, the types of media that were reported to have the most violations during the COVID-19 pandemic, the types of advertising/promotional violations and the fifth regions in Indonesia that reported the highest levels of offenses. The data analyzed is secondary data from the supervision of advertisements/promotions throughout Indonesia, collected from 2018 to September 5, 2021, obtained from the Directorate of Traditional Medicines and Health Supplements Control. The data was processed descriptively and using the chi-square method to see the significance, with the results that there were significant differences in advertising/promotion violations before and during the COVID-19 pandemic, the media that committed the most violations was internet media, with the highest type of violation being advertising/promoting products with exaggerated claims. The two regions in Indonesia that included the ten most extensive offenses before and during the COVID-19 pandemic were Jakarta and Makassar.